A different look at the soft topological polygroups - Mousarezaei, R.; Davvaz, B. (My University, 2022)
Soft topological polygroups are defined in two different ways. First, it is defined as a usual topology. In the usual topology, there are five equivalent definitions for continuity, but not all of them are necessarily established in soft continuity. Second it is defined as a soft topology including concepts such as soft neighborhood, soft continuity, soft compact, soft connected, soft Hausdorff space and their relationship with soft continuous functions in soft topological polygroups
Жұмсақ топологиялық полигруппаларға тағы бiр көзқарас
Другой взгляд на мягкие топологические полигруппы
Keywords: soft set; soft continuous; soft topological polygroups; soft Hausdorff space; soft open covering; soft compact; soft connected.